Kewarganegaraan sebagai Pilar Keberlanjutan Ekonomi Lokal: (Studi Literatur Kota Surakarta) - Putri Rizkia; Muhammad Arga Pangestu Antara; Wirda Rohmah (Badan Riset dan Inovasi Daerah Kota Surakarta, 2026)
This study aims to critically examine the role of citizenship as a pillar in supporting the sustainability of the local economy, focusing on the city of Surakarta as the case study. Using a literature review method, this research analyzes recent academic sources related to local economic development, citizen participation, local government policies, and relevant citizenship values in the context of sustainable development. The findings indicate that citizenship is not merely a legal status, but also reflects the active involvement of citizens in the planning, implementation, and evaluation of local economic policies. Citizen participation, supported by economic citizenship literacy, collaborative partnership models with the government, and responsive regulatory frameworks, significantly strengthens the legitimacy and effectiveness of local economic governance. On the other hand, the literature also highlights persistent challenges, such as limited citizen capacity, unequal access to information, and weak participatory institutions. Therefore, the role of the government is crucial in promoting meaningful citizen engagement through institutional strengthening and the integration of citizenship values into local regulations. This study offers both theoretical and practical insights for developing inclusive and sustainable local economic governance at the municipal level.